The Economic Impact of Agriculture and Natural Resources in Volusia County, Florida - Rodney L. Clouser; Mohammad Rahmani; W. David Mulkey (EDIS)
FE791, a 17-page report by Rodney L. Clouser, Mohammad Rahmani, and David Mulkey, provides a profile of agriculture and natural resource industries and an overview of their economic impacts in Volusia County, Florida. It is based on data from the IMPLAN Pro database for Florida counties for 2006, the 2002 Census of Agriculture, and the Volusia County Property Appraiser. Includes references. Published by the UF Department of Food and Resource Economics, February 2009.